Hubungan Beban Kerja dengan Burnout pada Perawat di Rumah Sakit Embung Fatimah Kota Batam Tahun 2024 - Fatmawasi Fatmawasi; Nelli Roza; Isna Aglusi Badri (Lembaga Pengembangan Kinerja Dosen, 2026)
Burnout is a condition of physical, emotional and mental exhaustion that occurs due to prolonged work pressure that is not well managed. Burnout is often experienced by individuals who work in environments with high demands, such as the health care sector. This study aims to identify the workload, burnout level, and the relationship between the two for nurses at the Embung Fatimah Regional General Hospital in 2024. Workload is measured by looking at the medium workload category, with 46.2% of nurses experiencing this workload. Burnout is measured using the Maslach Burnout Inventory (MBI) which consists of three dimensions: Emotional Exhaustion, Depersonalization, and Personal Accomplishment. The results showed that 76.9% of nurses experienced high Emotional Exhaustion, while 84.6% experienced Depersonalization with a low score. A total of 44.6% of nurses showed a high score on the Personal Accomplishment dimension. Statistical analysis shows that there is a significant relationship between workload and burnout in nurses. Emotional Exhaustion is related to moderate workload (p-value 0.023), but this relationship is not significant. Depersonalization is significantly related to a low burnout score (p-value 0.000), while Personal Accomplishment is related to a high burnout score, but this relationship is also not significant (p-value 0.041). This research suggests the need for attention to workload management and emotional support to reduce the risk of burnout, especially in the depersonalization dimension.